2019
DOI: 10.1016/j.imr.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicine of Tetun ethnic people in West Timor Indonesia: philosophy and practice in the treatment of malaria

Abstract: Background Interactions between humans and diseases for a long time have encourage people to construct concepts related to the disease and create strategies to prevent and treat the disease. The aim of this study is to document philosophy and practice of ethnomedicine of Tetun ethnic people in the prevention and treatment of malaria. Methods This research was a field study using ethnobotany and anthropology approaches. It was conducted among the Tetun people who settled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Miju-Mishmi people have also learned to apply the herbs to massage the body, including species viz., E. neriifolia, A. nervosa, C. tiglium, D. pentaphylla, E. phaseoloides. It is believed that, along with the oral administration, body massaging with certain herbs helps to reduce the body temperature, releasing sweats and relaxing the body muscles [39]. The UV index of the reported medicinal species ranges between 0.07 to 0.87.…”
Section: Quantitative Analysis Of Fl Pr Uv Icf and Fsmentioning
confidence: 99%
“…Miju-Mishmi people have also learned to apply the herbs to massage the body, including species viz., E. neriifolia, A. nervosa, C. tiglium, D. pentaphylla, E. phaseoloides. It is believed that, along with the oral administration, body massaging with certain herbs helps to reduce the body temperature, releasing sweats and relaxing the body muscles [39]. The UV index of the reported medicinal species ranges between 0.07 to 0.87.…”
Section: Quantitative Analysis Of Fl Pr Uv Icf and Fsmentioning
confidence: 99%
“…As is known, traditional treatment of malaria is a symptomatic healing with the main goal to reduce heat or fever, so it is possible that a plant used in the traditional treatment of malaria is more likely antipyretic than antiplasmodial. 21,22 The plants that have antimalarial properties can show a direct effect on Plasmodium by inhibiting the growth of Plasmodium or killing it, or giving indirect effects on the relationship between the human body and parasites. A plant that inhibiting or killing Plasmodium is called antiplasmodial or true antimalarial.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 1, 2021. ; https://doi.org/10.1101/2021.05.28.21258027 doi: medRxiv preprint 6 prevalence of the local community buying malarial medicines at a kiosk without consultation with health professionals [33]. Another study covering a Tetun community in Timor islands indicated the prevalence of community members applying various local medicinal plants to treat malaria [32]. One study representing the rural population in the province level indicated that more than half of the population delayed in seeking malaria treatment [34].…”
Section: Introductionmentioning
confidence: 99%
“…Limited investigations into malaria treatment-seeking behaviour had been conducted in the ENTP [21,[31][32][33][34]. One study drawing on a small sample at the sub-district level indicated that most participants sought care at health facilities after four days of the onset of symptoms [31].…”
Section: Introductionmentioning
confidence: 99%